MODELS OF HIGHER EDUCATION ACADEMIC PROGRAMMES REALIZED IN NETWORK FORM - Natalya V. Chicherina; Oksana D. Bugaenko (Высшее образование в России)
The article considers the issues of the design of higher education academic programmes which are realized in network form by educational and research organizations with the license for educational activities in the corresponding fields. The models of network form of academic programmes developed by the network of federal universities - "double degree", "resource center", "partnership network", "horizontal cooperation" - are described. Three cases are provided as illustrations of successful realization of the model "partnership network" at the bachelor and master levels.